The multidimensional orientation toward dying and death inventory: cross-cultural translation and validated in Mainland China participants - Yazhou Wang; Yuanheng Li; Yuzhuo Xie; Yuwei Zhang; Jingzhi Wang; Jiaqi Guo; Jiajun Shi; Mingxue Ma; Lu Zhao; Mingli Jiao (BMC Palliative Care)
Abstract Background The negative impact of over-treatment in end-of-life individuals has led to attention to the value of death. Reassessing the attitude of death and dying can improve care and improve the quality of life. Therefore, the use of multidimensional tools to comprehensively assess the attitudes of individuals on dying and death, identify attitude tendencies and causes meaningful, and evaluate the effectiveness of the tools is an important prerequisite. Objectives We aimed to obtain MODDI-F-C through cross-cultural translation and to evaluate its psychometric characteristics among mainland China participants. Methods In order to obtain MODDI-F-C, a cross-cultural translation of MODDI- F/eng was performed using the Brislin model. The items quality, factor structure, reliability and validity were assessed among 2105 participants from mainland China. The concurrent validity was assessed using the Chinese version of DAP-R for the first time. Results MODDI-F-C consists of 27 items, and five common factors were identified through factor analysis, accounting for 56.79% of the overall variance.The total consistency coefficient was 0.949.The correlation coefficient between DAP-R-C-Z and the overall scale was 0.55 (p < 0.001), between DAP - R-C - Z and the subscale 0.37–0.56 (p < 0.001).Most of the methods used for psychometric evaluation meet acceptable criteria. Conclusions Our research has initially confirmed that MODDI-F-C is an effective tool to evaluate the fear dimension of death and dying attitude, which can identify individuals’ tendencies and causes related to dying and death. However, the acceptance dimension needs further assessment.